Role of PSIP1/LEDGF/p75 in lentiviral infectivity and integration targeting. - Heather M Marshall; Keshet Ronen; Charles Berry; Manuel Llano; Heidi Sutherland; Dyana Saenz; Wendy Bickmore; Eric Poeschla; Frederic D Bushman (PLoS ONE)
Background To replicate, lentiviruses such as HIV must integrate DNA copies of their RNA genomes into host cell chromosomes. Lentiviral integration is favored in active transcription units, which allows efficient viral gene expression after integration, but the mechanisms directing integration targeting are incompletely understood. A cellular protein, PSIP1/LEDGF/p75, binds tightly to the lentiviral-encoded integrase protein (IN), and has been reported to be important for HIV infectivity and integration targeting. Methodology Here we report studies of lentiviral integration targeting in 1) human cells with intensified RNAi knockdowns of PSIP1/LEDGF/p75, and 2) murine cells with homozygous gene trap mutations in the PSIP1/LEDGF/p75 locus. Infections with vectors derived from equine infections anemia virus (EIAV) and HIV were compared. Integration acceptor sites were analyzed by DNA bar coding and pyrosequencing. Conclusions/significance In both PSIP1/LEDGF/p75-depleted cell lines, reductions were seen in lentiviral infectivity compared to controls. For the human cells, integration was reduced in transcription units in the knockdowns, and this reduction was greater than in our previous studies of human cells less completely depleted for PSIP1/LEDGF/p75. For the homozygous mutant mouse cells, similar reductions in integration in transcription units were seen, paralleling a previous study of a different mutant mouse line. Integration did not become random, however-integration in transcription units in both cell types was still favored, though to a reduced degree. New trends also appeared, including favored integration near CpG islands. In addition, we carried out a bioinformatic study of 15 HIV integration site data sets in different cell types, which showed that the frequency of integration in transcription units was correlated with the cell-type specific levels of PSIP1/LEDGF/p75 expression.